2014
DOI: 10.15252/msb.20145524
|View full text |Cite
|
Sign up to set email alerts
|

Causal signals between codon bias, mRNA structure, and the efficiency of translation and elongation

Abstract: Ribosome profiling data report on the distribution of translating ribosomes, at steady-state, with codon-level resolution. We present a robust method to extract codon translation rates and protein synthesis rates from these data, and identify causal features associated with elongation and translation efficiency in physiological conditions in yeast. We show that neither elongation rate nor translational efficiency is improved by experimental manipulation of the abundance or body sequence of the rare AGG tRNA. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
278
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(308 citation statements)
references
References 77 publications
21
278
3
Order By: Relevance
“…A genome-wide comparison of the in silico RNA structurome with experimental polysome profiling for allelic variants in hybrid mouse fibroblasts supports these assertions, as alleles with lower in silico-predicted mRNA secondary structure around the transcription start site had greater translation efficiency (defined as the ratio between ribosome-associated mRNA and total mRNA abundance) (37). Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2).…”
Section: Stability and Degradationmentioning
confidence: 78%
“…A genome-wide comparison of the in silico RNA structurome with experimental polysome profiling for allelic variants in hybrid mouse fibroblasts supports these assertions, as alleles with lower in silico-predicted mRNA secondary structure around the transcription start site had greater translation efficiency (defined as the ratio between ribosome-associated mRNA and total mRNA abundance) (37). Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2).…”
Section: Stability and Degradationmentioning
confidence: 78%
“…Experiments without CHX, on the other hand, report positive correlations of varying magnitude (Fig 1D, 0x Gerashchenko NAR points and purple labels). Experiments by Pop [36], Lareau [26], Nedialkova [29], Guydosh [35] and Gardin [33] produce weak to moderate correlations, but experiments by Gerashchenko [34], Jan [41], Williams [42], Weinberg [38], and Young [37] produce fairly strong and highly statistically significant correlations.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmmentioning
confidence: 98%
“…An alternative experimental protocol uses an optimized harvesting and flash-freezing process that allows CHX pretreatment to be omitted [15,17,26,29,[33][34][35][36][37][38]. Experiments performed with this protocol have revealed that treatment with CHX affects several high-level characteristics of footprinting data, including the distribution of lengths of nuclease-protected fragments in mammalian cells [39] and the amount of enrichment in ribosome density at the 5' end of coding sequences in yeast [34].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tRNA pool in mammals appears to be equally efficient at translating any transcriptome, regardless of cell type or condition (Rudolph et al 2016). While some works have suggested that preferentially used codons are not translated faster than unpreferred ones or that rare codons do not correlate with ribosome pausing (Qian et al 2012;Guo et al 2010;Pop et al 2014), other reports have suggested that differences in tRNA population are associated with diverse effects on translation (Lampson et al 2013;Goodarzi et al 2016). This is the case of a mutation of a tissue-specific tRNA expressed in the mouse nervous system, which led to ribosome stalling and that was implicated as the cause of neurodegeneration (Ishimura et al 2014).…”
Section: Translation Kineticsmentioning
confidence: 99%